Image theory for electromagnetic sources in chiral medium above the soft and hard boundary. - Lindell, I.V (IEEE Transactions on antennas and propagation)
The classical image theory valid for electromagnetic (EM) sources in an isotropic medium above a planar perfect electric conductor (PEC) or perfect magnetic conductor (PMC) surface was extended to involve the planar soft-and-hard surface (SHS) boundary that can be realized with tuned corrugations. The image principle is now generalized to EM sources in isotropic chiral medium above an SHS boundary. The problem is solved by two consecutive decompositions of the sources reducing the problem to four classical ones involving electric and magnetic sources above PEC and PMC boundaries; each involving an isotropic nonchiral medium and possessing a known image solution. One of the decompositions is based on the fact that the two eigenwaves of a chiral medium do not couple at a soft-and-hard surface; and, the other one, on the eigenpolarizations of the reflection dyadic